Fog and other stories - Lowe, Bill (Oxford University Press, 1992)
The "Bell in the Fog" is the tale of an author who buys a country estate. Along with the property come a furnished house -- and, of course, two paintings. They are paintings of a young boy and girl, siblings who died in childhood. When Orth -- the author -- sees these paintings, they begin to haunt his every thought until they finally become flesh and bone